Transport platform stabilization mechanism using controlled suspension - Iliushina, Anna; Druk, Alexander (Institute of Advanced Engineering and Science, 2024)
In this paper the authors present the development of a novel transport mechanism designed to perform gravity survey work on difficult terrain. Thus, in the first part of the paper the authors present review and analysis of existing patents and commercial developments of transport platforms capable of stabilizing loads while travelling in urban environments with potholes and steps. In the second part we present technical solution of a steerable suspension with a torsion bar as an elastic element based on the elimination of the drawbacks of the existing developments. The core feature of this development is the potential ability to adapt the suspension to different types of surfaces by changing the elastic characteristics of the torsion bar. We also propose an alternative to the generally accepted kinematic scheme by using a conical gearbox, which allows to achieve a tight arrangement of suspension mechanisms within the dimensions of the transport platform. In addition, authors propose the stabilization mechanism, that allows to change the clearance of the transport platform and provides stabilization of the gravity exploration research equipment, characterized by sensitivity to deviations from the vertical.